Telaah Peran Etis Agama-agama di Indonesia Perspektif Civil Religion - Syakur, Abd. (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
This article seeks to figure out socio-religious reciprocity pertinent to the pluralistic context of Indonesia within its various dimensions of life, especially the religious aspect, through what so-called civil religion. The very notion of civil religion reflects religious, social, and political maturity. The religions, in this context, function as a pivotal source of moral-ethics which generate spirit to build a strong nation-state to pursue its objectives. At this point, the state becomes a shared sacred home to all of its citizens which is free of fear and anxiety. The state plays an undoubtedly important role to protects its people and provide them a means of development in order to allow them to exhume religious freedom and reach a holy meaningful life. It will subsequently enhance and strengthen culture of dialog. This article supports an argument that in order to bring about the vision of civil religion in Indonesia we require three least possible conditions, namely heterogeneous religions which generate positive morality, the culture of sincere dialog, and freedom of religion.